The Effect of Development Programs on Employees Satisfaction in Andhra Pradesh Manufacturing Industries - E. Hari Prasad, Prof P. Raghunadha Reddy (Journal of Informatics Education and Research, 2025)
The present study investigates the effect of development programs on employee satisfaction in manufacturing industries of Andhra Pradesh. Four dimensions of development programs—skill development, career development opportunities, personal development initiatives, and on-the-job training and mentoring—were identified as independent variables, while employee satisfaction was considered as the dependent variable. A sample of 200 employees was surveyed using a structured questionnaire, and the collected data were analyzed through descriptive statistics, tests of normality, Pearson correlation, ANOVA, and regression analysis. The findings revealed that skill development programs had a significant positive impact on employee satisfaction, explaining nearly one-fourth of its variance. Career development opportunities also showed a strong positive relationship, accounting for 28% of the variance in employee satisfaction. Further, personal development initiatives and on-the-job training and mentoring demonstrated moderate but significant correlations with employee satisfaction. These results confirm that comprehensive development programs contribute meaningfully to enhancing employee satisfaction in the manufacturing sector. The study emphasizes the need for manufacturing units in Andhra Pradesh to invest in systematic and continuous development initiatives, as they not only improve employee satisfaction but also strengthen organizational performance and sustainability.